Comparative Anthelmintic Efficacy of Pineapple and Neem Leaves in Broiler Chickens Experimentally Infected with Ascaridia galli - Patra, Gautam; Lyngdoh, W.M.; Ali, M. Ayub; Prava, M.; Chanu, Kh. Victoria; Tolenkhomba, T.C.; Das, Gunjan; Prasad, H.; Devi, L. Inaotombi; Devi, Irungbam Karuna (International Journal of Poultry Science, 2010)
A study was carried out in broiler chicken for comparative anthelmintic efficacy of neem and pineapple leave powder with piperazin hydrate for treatment of experimental Ascaridia galli infection. The affected birds had lower levels of Hb, PCV, Ca and P. The profile changed after treatment with neem and pineapple leave powder which was comparable to that observed after treatment with piperazine hydrate. Neem and pineapple leave powder treatment caused cent percent evacuation of the worms on 28th and 56th day post treatment respectively.